Indicators for evaluation of commissions managers of water systems and its application in analysis of metropolitan watershed of Fortaleza - ClÃa Rocha Rodrigues (2014)
Essential to life on the planet, water has fundamental importance as social and economic development factor, being the focus of several conflicts and interests. The gap between water needs and availability worldwide is undoubtedly one of the main problems of today. This situation requires a very effective management of water resources. CearÃ state adopted the model that proposes an integrated, decentralized and participatory water management and that has the River Basin as planning unit. In general, the following main levels of participation can be mentioned: the State council of Water Resources - CONERH, River Basin Committees, Commissions of PerennializedValleys WaterUsers and Managing Commissions of Water Systems. The objective of this work is to formulate and to apply indicators to assess the participation of the Managing Commissions in managing Metropolitan Basinsâ waters, taking as case study the Managing Commissions of the following water systems: Castro, Acarape do Meio and ChorÃ. To accomplish this, documental and bibliographic research were used, as well as application of questionnaires. The methodology followed a sequence composed of four phases: definition of the evaluation indicators system, application of the Delphi method, application of the hierarchic analysis of processes (AHP) and construction of the evaluation index for the water systems management commissions. The application of the Delphi method was attended by 14 (fourteen) technical specialists in water resources and the evaluation of the researched committees was attended by 24 (twenty four) members. The research has defined the relevant aspects or dimensions to be considered for assessment of this management sphere, which are: the existence of financial resources, planning, commitment of the members of the Managing Commissions, qualification of the members of the Managing Commissions, infrastructure for the functioning of the Managing Commissions, interaction with other spheres of management, transparency of management bodies, performance of the Managing Commissions, representativeness and credibility. The seventy-five indicators identified from these dimensions supported the evaluation of the Managing Commissions under study, allowing to identify in the interpretation of the results that these commissions are active in the management of metropolitan basins and contribute to the negotiated allocation of water from the referred basin. However, some limitations must be passed to become fully effective.